The Voice of the Forest Sisters: (Un)known Experiences in Diana Glemžaitė’s Poetry - Katkuvienė, Jurgita (Colloquia, 2026)
The article examines the most mature works of Diana Romualda Glemžaitė (1925–1949) from the last two years of her life, written while she was living in hiding, working as a liaison, and after she had become a partisan. The experiences revealed in the poems are discussed as structures of poetic expression of the partisan war. The article inquires of their authenticity, the semantic boundaries of partisan literary texts, and the codes for reading war literature. The interpretation is grounded in the reciprocal relationship between text and context suggested by literary sociologist Dominique Maingueneau, drawing on his concept of paratopic shifter and employing the principles of semiotic analysis. Glemžaitė’s literary legacy, which has been omitted from the studies of partisan literature, brings up a matter of the significance of female authorship. Adhering to the premise that in partisan literature there is an indisputable connection between the speaker of a poem and the person who wrote it, the author of the article turns to materials that construct a biographical discourse (memoirs, letters, archival creative materials, and historical research). When interpreting the texts, the focus is on experiences related to the problem of perception that emerged in Glemžaitė’s poetry during the period under consideration, which unfolds along two trajectories: as a general question of choosing the partisan path and understanding that choice, and as a specific one – a woman’s choice. In the first case, the experiences of partisan life are revealed through the us vs them divide, wandering, homelessness, a sense of radical transformation, and an active love of the homeland. In the second case, it is manifested through an evaluation specific to women and partisan motherhood. These spatial elements, characters, behavioral patterns, and other features appear in Glemžaitė’s poetry as paratopic shifters.